Induction heating technology for improving compaction of asphalt joints. Issue 12 (14th October 2020) - Bueno, Moises; Arraigada, Martin; Partl, Manfred N.
ABSTRACT: Longitudinal and transversal joints in asphalt roads are permanently present in any pavement structure due to the construction procedures applied nowadays. These types of joints form discontinuities in the aggregate skeleton affecting the traffic loads distribution. Nevertheless, conventional joints construction procedures are basically focused on sealing the interface of the joint to avoid water infiltration. This study investigates the influence of the compaction temperature and the geometry of different joint designs. In particular, it proposes a new approach where iron particles are added to the asphalt mixture for allowing an induction heating process that locally increases the temperature either during the compaction of the joint or for an extra-compaction after construction of the joint. Results confirmed that high temperature during compaction of the joint leads to a better overall performance and that angular joints improve the interlock between the two interfaces. Likewise, it was shown that an extra-compaction process can significantly enhance the resistance of untreated joints against fracture and adhesion loss.